2000
DOI: 10.1097/00007632-200001010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fusion Rates With Cervical Plating for Two-Level Anterior Cervical Discectomy and Fusion

Abstract: Study Design. A retrospective review of all patients surgically treated with a two-level anterior cervical discectomy and fusion with and without anterior plate fixation by a single surgeon.Objectives. To compare the clinical and radiographic success of two-level discectomy and the effect of anterior cervical plate fixation.Summary of Background Data. Prior studies of multisegment fusions have shown decreased fusion rates correlating with the number of increased levels. The use of anterior plates for single-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
150
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(165 citation statements)
references
References 10 publications
(5 reference statements)
2
150
0
9
Order By: Relevance
“…Geisler et al [29] reported a 100 % fusion rate in 35 plated multilevel (three-and four-level) ACDFs. Wang et al [30] found that 18 % (7 of 40) of the patients had pseudarthrosis after three-level plated ACDF, and they observed no difference in fusion rates between plated and nonplated subgroups. Bolesta et al [3] reported a nonunion rate of 53 % (8/15 patients) for plated ACDF, the highest in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geisler et al [29] reported a 100 % fusion rate in 35 plated multilevel (three-and four-level) ACDFs. Wang et al [30] found that 18 % (7 of 40) of the patients had pseudarthrosis after three-level plated ACDF, and they observed no difference in fusion rates between plated and nonplated subgroups. Bolesta et al [3] reported a nonunion rate of 53 % (8/15 patients) for plated ACDF, the highest in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [5] found that ACDF with a cage and plate construct led to a high fusion rate in the treatment of single-level degenerative cervical disease and also led to acceptable intervertebral disc space and lordosis. Emery et al [4] and Wang et al [30] studied the development of pseudoarthrosis after multilevel fusion without plate augmentation, and both reported high pseudoarthrosis rates of 44 and 37 %, respectively. Papadopoulos et al [31] implemented plate augmentation in multilevel fusions and found that only two of their 46 cases (4 %) developed pseudoarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multilevel stand-alone cages were reported to be associated with high rates of pseudarthrosis [32]. To increase fusion rates, prevent subsidence and restore cervical sagittal alignment, additional anterior cervical plating has been recommended for cage fixation [29].…”
Section: Discussionmentioning
confidence: 99%
“…Because of increased biomechanical stress and the number of bony interfaces, the pseudoarthrosis rate after a multisegmental anterior cervical fusion is directly correlated with the number of levels treated [11,22]. In 1997, Emery et al retrospectively reviewed 16 patients undergoing anterior cervical discectomy and stand-alone graft fusion for three-level disease.…”
Section: Union and Pseudoarthrosismentioning
confidence: 99%